PENGENDALI LOGIKA FUZZY SUHU HIPERTERMIA BERBASIS VISUAL BASIC DAN AKUISISI BERBASIS USB - Andi Kurniawan Nugroho (Prosiding SNST Fakultas Teknik, 2010)
Therapy using heat (Hyperthermia) have drawn attention and have been done in so many form. The controlling of Hyperthermia temperature determines the therapy efficiency with the thermal effect. This matter is needed so that the obtained result of optimal therapy without generating loss off destruction of healthy cell.PID Controller which is used in conducting temperature felt still have an inconvenieal overshoot and also oscillation. Something else that becoming constraint is very complicated mathematical model. The aim of this research is to prove that by using fuzzy logic will minimize the overshoot value so that the result is accurate in determination of temperature set point (43oC). The steps of these research are : doing the sensor compensation, measuring the output voltage of sensor amplifier, determining the regression coefficients value to find the linear regression equation, determining the deviation standard into Visual Basic 6 program, to interface between the computer and the USB 1208LS through Instacal program, classifying the control of Fuzzy Logic. The conclusions of this research are : the more the number of iteration (temperature increasing), the smaller error, d_error and d_temperature value can get. The using of fuzzy rule and the boundaries of membership value, which not accurate can affect the stability and the system response speed. The life and dead time of the magnetron are determined by the duty cycle that will be put into the graph of membership function, delta_temperature (u). The higher value of the duty cycle, the longer life time that compared to the dead time. Keywords : temperature, hyperthermia, fuzzy logic, USB, duty cycle.